HUBUNGAN KEKUATAN MENGGENGGAM DENGAN MOBILITAS PADA LANSIA - Natalia Pristika Sembiring Brahmana (2022)
The elderly is an advanced stage that is passed in the process of life in every human being which is characterized by a decrease in the ability and function of his body both physically and psychologically Changes that occur in the musculoskeletal system are a decrease in muscle mass, weakened muscle strength and decreased mobility. Decreased muscle strength can lead to decreased mobility ability while decreased mobility in the elderly will have a big impact on daily activities. The purpose of this study was to find out the relationship between grasping power and mobility in the elderly. This study used descriptive research correlation with cross sectional models. The measuring instrument used to measure grasping strength is the Hand Grip Dynamometer and to measure mobility is the Time Up and Go Test, and a large sample of 35 elderly people in the Dahlia Senja Community. The data analysis used is univariate and bivariate analysis. The results of research that has been conducted using the spearman rho correlation test method can be concluded that there is no relationship of grasping power with mobitas in the elderly. Conclusions are suggested with a larger number of samples and more precise research screening, to be able to search for a wider range of respondent characteristics that are expected to be wider.